Ultrasonography in the diagnosis of obesity in cats and its correlation with fructosamine and lipid levels - Buso, Jéssica; Ventura, Bruno; Vieira, Jhulya; Moreira, Luciano; Pedrosa, Poliana; Vale, Isabelly; Cruz, Igor; Aptekmann, Karina (Archives of Veterinary Science, 2023)
The aim of this study was to determine whether ultrasound imaging is an efficient method to assess subcutaneous fat in cats, the anatomical sites where more significant fat deposition occurs, and if there is a correlation between subcutaneous fat thickness and serum levels of cholesterol, triglycerides, and fructosamine. A total of 30 healthy adult cats were used and divided into three groups of 10 animals each, based on the estimated body condition score (BCS). The ideal group (IG) included cats with BCS 3; the overweight group (OWG), with BCS 4; and the obese group (OG), with BCS 5. Ultrasonographic measurement of subcutaneous fat was conducted in five anatomical regions: lumbar, abdominal, thoracic, femoral, and pectoral. We observed that obese cats had greater fat deposition in the abdominal and thoracic regions when compared to those with ideal weight, and that cholesterol and triglyceride levels were higher with the increase in subcutaneous fat thickness in the thoracic region. Nonetheless, there were no differences in fat deposition in the OWG compared to cats from the IG and OG. Ultrasonography made it possible to associate cholesterol and triglyceride levels with local fat deposits and to differentiate obese cats from those with ideal weight by analyzing the thickness of subcutaneous fat in the abdominal and thoracic regions, making this method efficient and less subjective.